1997
DOI: 10.2190/p7ql-4g11-qgh5-l891
|View full text |Cite
|
Sign up to set email alerts
|

Student Study Choices in the Principles of Economics: A Case Study of Computer Usage

Abstract: Principles of Economics students at Mississippi State University were provided the opportunity to use computer assisted instruction (CAI) as a supplemental study activity. Students were free to choose the extent of their computer work. Throughout the course, weekly surveys were conducted to monitor the time each student spent with their textbook, computerized tutorials, workbook, class notes, and study groups. The surveys indicated that only a minority of the students actively pursued CAI. Probit and OLS model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The number of hours per week which computers were used revealed some interesting trends. There was a significant positive correlation of age of the a similar finding among economics students by Grimes, Sanderson, and Ching [13]. This result was also reflected in the significant difference in the total numer of hours and graduate/undergraduate status.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The number of hours per week which computers were used revealed some interesting trends. There was a significant positive correlation of age of the a similar finding among economics students by Grimes, Sanderson, and Ching [13]. This result was also reflected in the significant difference in the total numer of hours and graduate/undergraduate status.…”
Section: Discussionsupporting
confidence: 73%
“…That this survey sample seems to go against trends seen in the general population of computer ownership based on ethnicity points to education level rather than ethnicity being a stronger factor in determining computer use/ownership [16]. Still Grimes, Sanderson, and Ching [13] found that among economics majors African Americans used computers less for class work. Breaking down computer use by school, work, and leisure activities begins to show some differences in full and part-time status.…”
Section: Discussionmentioning
confidence: 91%